The global burden of otitis media in 204 countries and territories from 1992 to 2021: a systematic analysis for the Global Burden of Disease study 2021 - Huang, Guan-Jiang; Lin, Bao-Rui; Li, Pei-Shan; Tang, Na; Fan, Zhi-Jun; Lu, Biao-Qing (Frontiers in Public Health, 2025)
ObjectivesThis study aims to analyze the global burden of otitis media and predict future trends using data from the Global Burden of Disease 2021 (GBD 2021).Study designA cross-sectional analysis of GBD 2021 results was conducted.MethodsAge-standardized incidence rates (ASIR), age-standardized prevalence rates (ASPR), and age-standardized disability-adjusted life years (DALYs) rates (ASDR) were calculated. Trend analysis was conducted using estimated annual percentage change (EAPC), Joinpoint regression, age-period-cohort, and decomposition analyses. Future projections were generated using Bayesian age-period-cohort (BAPC) and auto-regressive integrated moving average (ARIMA) models.ResultsThe global incidence of otitis media rose from 322.1 million cases in 1992 to 391.3 million in 2021, with ASIR increasing slightly from 5345.09 to 5529.1 per 100,000 (EAPC: 0.11%). Despite this increase, the ASPR decreased from 1786.56 to 1593.74 (EAPC: -0.43%). DALYs increased from 2.16 million to 2.48 million; however, ASDR declined from 37.68 to 32.54 per 100,000 (EAPC: −0.51%). Notably, low and low-middle SDI regions showed significant disparities, with higher ASIRs (up to 5315.08 for males) but declining trends in ASPR. Regionally, East Asia exhibited the most substantial decline in ASPR (−1.14%) and ASDR (−1.22%), while Central Sub-Saharan Africa demonstrated stable ASDR. Future projections indicate a rising ASIR and declining ASPR and ASDR through 2036.ConclusionThe global burden of otitis media shows significant regional disparities, with stable incidence but declining prevalence and DALYs rate. Public health interventions have been effective in higher SDI regions, but targeted efforts are needed in low and low-middle SDI regions to further reduce the burden of otitis media.